Advances in self-powered triboelectric pressure sensors. Issue 36 (30th July 2021) - Lei, Hao; Chen, Yunfeng; Gao, Zhenqiu; Wen, Zhen; Sun, Xuhui
Abstract : Triboelectric pressure sensors arouse great interest in wearable electronics due to their self-powered property. Here, recent key advancements of triboelectric pressure sensors are comprehensively reviewed and some future trends are also discussed. Abstract : Pressure sensors have attracted much attention for their potential applications in health monitoring, wearable devices, electronic skins, smart robots, etc . With the rapid development of the Internet of Things, considering the large number and small scale of sensors, power consumption has become a key factor in large-scale applications. A new generation of self-powered pressure sensors based on a triboelectric nanogenerator has been developed in terms of its incomparable advantages in power consumption and potential performance. Based on the coupling effects of triboelectrification and electrostatic induction, it enables obtaining information on the mechanical input, e.g., magnitude and frequency, by analyzing the electrical output signals. Intensive efforts have been devoted to improving the sensing performance of triboelectric pressure sensors to meet the demands of practicality. In this review, the key advancements in materials, structures and applications of self-powered triboelectric pressure sensors are systematically reviewed. Then, the theoretical basis, impact mechanism and approaches to optimize the pressure sensing performance have been comprehensively analyzed. Finally, the future perspectives of self-powered triboelectric pressure sensors have also been discussed.